Ultrahigh-temperature ceramic composite material and preparation method thereof

By mixing graphene with ultra-high temperature ceramic powder and using the graphene wrapping mechanism to suppress grain growth during the sintering process, the problems of low deposition efficiency and uneven sintering in the prior art are solved, and more uniform heat treatment and Performance improvement.

CN119430952APending Publication Date: 2025-02-14GUILIN UNIV OF ELECTRONIC TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411690830.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the existing preparation methods for ultra-high temperature ceramic composite materials, the chemical liquid phase vaporization deposition process has low deposition efficiency and long deposition period, which cannot improve the deposition rate and ensure uniformity of deposition along the depth direction. Moreover, ceramic powders are prone to heat during sintering. The problem is even.

Method used

By mixing graphene with ultra-high temperature ceramic powder, and using the graphene wrapping mechanism during the sintering process, the thermal conductivity of the ceramic powder is improved, and the composite powder is heated more uniformly during the sintering process.

Benefits of technology

It effectively inhibits grain growth, improves the thermal conductivity and sintering uniformity of ceramic composite materials, and improves the performance stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430952A_ABST
    Figure CN119430952A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: step 1, preparing a suspension, step 2, mixing powder, uniformly mixing ultrahigh-temperature ceramic powder and a sintering aid according to a mass ratio of 1: (2.5-3.5) to obtain a mixture A, step 3, carrying out ball milling and wet mixing to obtain a mixture B, and step 4, drying, namely drying the mixture B in a vacuum drying oven to obtain the ultrahigh-temperature ceramic composite material. Step 6, sintering: putting the pre-pressed graphite mold into a sintering furnace cavity, and sintering to obtain the ultra-high-temperature ceramic composite material. According to the invention, when graphene is mixed with ultra-high-temperature ceramic powder and is compactly sintered, rearrangement of ceramic particles is caused in the initial stage of sintering, grain growth is obviously inhibited by using a wrapping mechanism of graphene, and the thermal conductivity of the ceramic powder is effectively improved through the physical characteristics of graphene due to the fact that a carbon structure of graphene plays a role in sintering in the later stage of sintering; and the composite powder is heated more uniformly in the sintering process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ultra-high temperature ceramic materials, and in particular to an ultra-high temperature ceramic composite material and a preparation method thereof. Background Art

[0002] Ultra-high temperature ceramic composites are a type of advanced materials that can maintain stable performance in extremely high temperature environments. Ultra-high temperature ceramic composites are usually composed of fibers, interfaces and ultra-high temperature ceramic matrices. Among them, the ultra-high temperature ceramic matrix is ​​the main high temperature resistant component, and common ones are borides and carbides. Fiber materials generally play a role in strengthening and toughening, such as carbon fibers. The interface phase is the part that connects the fiber and the matrix, and has an important influence on stress transfer and the overall performance of the composite material.

[0003] The invention patent with application number 202010925331.1 discloses an ultra-high temperature ceramic composite material and a preparation method thereof, which is prepared by boron thermal reaction using transition metal oxide and boron powder as raw materials (Hf 0.25 Ta 0.25 Zr 0.25 Ti 0.25 )B 2 Ceramic powder, compared with commercially available borides, is smaller in size, higher in purity and more uniform in composition. The introduction of SiC as an additive promotes the sintering of high-density ceramics, reduces the sintering temperature, and inhibits grain growth. The gas phase siliconization process can effectively fill the pores and other defects in the ceramics through the infiltration of Si vapor, and finally quickly form a high-density (Hf 0.25 Ta 0.25 Zr 0.25 Ti 0.25 )B 2 -SiC-Si composite materials;

[0004] However, the chemical liquid phase vapor deposition process in the above-mentioned ultra-high temperature ceramic composite material and preparation method has low deposition efficiency and long deposition cycle, and cannot improve the deposition rate and ensure the uniformity of deposition along the depth direction. It is easy to grow grains during sintering, which affects the performance of the composite material. The ceramic powder is prone to uneven heating during sintering in the above-mentioned ultra-high temperature ceramic composite material and preparation method. Summary of the invention

[0005] In view of the above problems, the purpose of the present invention is to propose an ultra-high temperature ceramic composite material and a preparation method. When the ultra-high temperature ceramic composite material and the preparation method are mixed with ultra-high temperature ceramic powder and densely sintered through the characteristics of graphene, the ceramic particles are rearranged in the early stage of sintering, and the grain growth is significantly inhibited by the wrapping mechanism of graphene. In the later stage of sintering, its carbon structure plays a sintering role, and the thermal conductivity of the ceramic powder is effectively improved through the physical properties of graphene, so that the composite powder is heated more evenly during the sintering process.

[0006] To achieve the purpose of the present invention, the present invention is implemented by the following technical solutions: an ultra-high temperature ceramic composite material and a preparation method. In a first aspect, an embodiment of the present invention provides a preparation method of a high temperature ceramic composite material, comprising the following steps:

[0007] Step 1: preparing a suspension, mixing graphene powder with deionized water at a mass ratio of 0.3 to 5:1 to prepare a solution, placing the solution in an ultrasonic generator for ultrasonic treatment at a frequency of 150 kHz, and then centrifuging the solution in a centrifuge at a speed of 3000 r / min, taking the supernatant to obtain a graphene suspension;

[0008] Step 2: Mixing powders: uniformly mixing ultrahigh temperature ceramic powder and sintering aid in a mass ratio of 1:2.5-3.5 to obtain a mixture A;

[0009] Step 3: ball milling wet mixing: adding the graphene suspension and zirconium oxide grinding balls to the mixture A, and ball milling on a planetary ball mill to obtain a mixture B;

[0010] Step 4: Drying: Drying the mixture B in a vacuum drying oven to obtain a dry powder C;

[0011] Step 5: Filling the mold, screening the powder C to obtain powder with uniform particles and pouring it into a graphite mold, padding the upper and lower parts of the mold with carbon paper, placing a pressure head, and pre-pressing it on a hydraulic pump to obtain a green body D;

[0012] Step 6: Sintering: Place the pre-pressed graphite mold into the sintering furnace chamber, close the valve, evacuate to less than 10 MPa, and start sintering in two stages. After sintering, grind the surface of the green body D to obtain an ultra-high temperature ceramic composite material.

[0013] A further improvement is that the ultra-high temperature ceramic powder in step 2 is zirconium diboride, whose chemical formula is ZrB 2 The sintering aid in step 2 is silicon carbide, whose chemical formula is SiC.

[0014] A further improvement is that the ball milling speed in step three is 300 to 500 r / min, and the ball milling time is 5 to 10 hours.

[0015] A further improvement is that the drying time in step 4 is 8 to 12 hours and the drying temperature is 80 to 120°C.

[0016] A further improvement is that the pre-pressing pressure in step five is 20 MPa and the pre-pressing time is 10 min.

[0017] A further improvement is that the sintering heating rate in step six is ​​5-15°C / min, the first sintering temperature is 1800°C, and the second sintering temperature is 2150°C.

[0018] In a second aspect, an embodiment of the present invention provides an ultra-high temperature ceramic composite material, which is prepared according to any method described in the first aspect.

[0019] The beneficial effects of the present invention are as follows: when the present invention mixes the ultra-high temperature ceramic powder with the characteristics of graphene and densely sinters, the ceramic particles are rearranged in the early stage of sintering, and the grain growth is significantly inhibited by the wrapping mechanism of graphene. In the later stage of sintering, its carbon structure plays a sintering role, and the thermal conductivity of the ceramic powder is effectively improved by the physical properties of graphene, so that the composite powder is heated more evenly during the sintering process. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a process flow chart of the present invention; DETAILED DESCRIPTION

[0021] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0022] Embodiment 1:

[0023] The following steps are involved:

[0024] Step 1, preparation of suspension, mixing graphene powder with a mass ratio of 0.3:1 with deionized water to prepare a solution, placing it in an ultrasonic generator for ultrasonic treatment at a frequency of 150kHz, and then transferring it into a centrifuge for centrifugation at a speed of 3000r / min, using a mechanical exfoliation method, through mechanical stirring, ultrasonic treatment, etc., to exfoliate the graphite flakes and disperse them in the solvent to form a graphene suspension, and taking the upper clear liquid to obtain a graphene suspension;

[0025] Step 2: Mixing powders: uniformly mixing ultrahigh temperature ceramic powder and sintering aid in a mass ratio of 1:2.5 to obtain a mixture A;

[0026] Ultra-high temperature ceramic powder is zirconium diboride, whose chemical formula is ZrB 2 ,The sintering aid in step 2 is silicon carbide, whose chemical formula is SiC.

[0027] Step 3: ball milling wet mixing: adding the graphene suspension and zirconium oxide grinding balls to the mixture A, and ball milling on a planetary ball mill to obtain a mixture B;

[0028] The ball milling speed is 300 r / min, the ball milling time is 5 hours, and the graphene and ceramic powder are fully mixed by mechanical stirring.

[0029] Step 4: Drying: Drying the mixture B in a vacuum drying oven to obtain a dry powder C;

[0030] The drying time is 8 hours, the drying temperature is 80° C., and the dried powder C is a composite powder in which graphene and ceramic powder are uniformly mixed.

[0031] Step 5: Filling the mold, screening the powder C to obtain powder with uniform particles and pouring it into a graphite mold, padding the upper and lower parts of the mold with carbon paper, placing a pressure head, and pre-pressing it on a hydraulic pump to obtain a green body D;

[0032] The preloading pressure is 20MPa and the preloading time is 10min.

[0033] Step 6: Sintering: Place the pre-pressed graphite mold into the sintering furnace chamber, close the valve and evacuate to less than 10 MPa to start sintering at two temperatures, and grind the surface of the green body D after sintering to obtain an ultra-high temperature ceramic composite material;

[0034] The sintering heating rate was 5°C / min, the first sintering temperature was 1800°C, and the second sintering temperature was 2150°C.

[0035] Under 500°C conditions, after the introduction of graphene, the thermal shock test of the ceramic composite material sample can retain 79% of the initial strength value.

[0036] The composite material was processed into high-temperature tensile specimens. According to GJB8736-2015 test method for room-temperature tensile properties of continuous fiber reinforced ceramic matrix composites, the tensile strength at 1800°C was 225MPa.

[0037] Embodiment 2:

[0038] The following steps are involved:

[0039] Step 1, preparation of suspension, mixing graphene powder with deionized water at a mass ratio of 3:1 to prepare a solution, placing it in an ultrasonic generator for ultrasonic treatment at a frequency of 150kHz, and then transferring it into a centrifuge for centrifugation at a speed of 3000r / min, using a mechanical exfoliation method, through mechanical stirring, ultrasonic treatment, etc., to exfoliate the graphite sheets and disperse them in the solvent to form a graphene suspension, and taking the upper clear liquid to obtain a graphene suspension;

[0040] Step 2: Mixing powders: uniformly mixing ultrahigh temperature ceramic powder and sintering aid in a mass ratio of 1:3 to obtain a mixture A;

[0041] Ultra-high temperature ceramic powder is zirconium diboride, whose chemical formula is ZrB 2 ,The sintering aid in step 2 is silicon carbide, whose chemical formula is SiC.

[0042] Step 3: ball milling wet mixing: adding the graphene suspension and zirconium oxide grinding balls to the mixture A, and ball milling on a planetary ball mill to obtain a mixture B;

[0043] The ball milling speed is 400 r / min, the ball milling time is 8 hours, and the graphene and ceramic powder are fully mixed by mechanical stirring.

[0044] Step 4: Drying: Drying the mixture B in a vacuum drying oven to obtain a dry powder C;

[0045] The drying time is 10 hours, the drying temperature is 100° C., and the dried powder C is a composite powder in which graphene and ceramic powder are uniformly mixed.

[0046] Step 5: Filling the mold, screening the powder C to obtain powder with uniform particles and pouring it into a graphite mold, padding the upper and lower parts of the mold with carbon paper, placing a pressure head, and pre-pressing it on a hydraulic pump to obtain a green body D;

[0047] The preloading pressure is 20MPa and the preloading time is 10min.

[0048] Step 6: Sintering: Place the pre-pressed graphite mold into the sintering furnace chamber, close the valve and evacuate to less than 10 MPa to start sintering at two temperatures, and grind the surface of the green body D after sintering to obtain an ultra-high temperature ceramic composite material;

[0049] The sintering heating rate was 10°C / min, the first sintering temperature was 1800°C, and the second sintering temperature was 2150°C.

[0050] Under 500°C conditions, after the introduction of graphene, the thermal shock test of the ceramic composite material sample can retain 85% of the initial strength value.

[0051] The composite material was processed into high-temperature tensile specimens. According to GJB8736-2015 test method for room-temperature tensile properties of continuous fiber reinforced ceramic matrix composites, the tensile strength at 1800°C was 203 MPa.

[0052] Example 3

[0053] The following steps are involved:

[0054] Step 1, preparation of suspension, mixing graphene powder with deionized water at a mass ratio of 5:1 to prepare a solution, placing it in an ultrasonic generator for ultrasonic treatment at a frequency of 150kHz, and then transferring it into a centrifuge for centrifugation at a speed of 3000r / min, using a mechanical exfoliation method, through mechanical stirring, ultrasonic treatment, etc., to exfoliate the graphite flakes and disperse them in the solvent to form a graphene suspension, and taking the upper clear liquid to obtain a graphene suspension;

[0055] Step 2: Mixing powders: uniformly mixing ultrahigh temperature ceramic powder and sintering aid in a mass ratio of 1:3 to obtain a mixture A;

[0056] Ultra-high temperature ceramic powder is zirconium diboride, whose chemical formula is ZrB 2 ,The sintering aid in step 2 is silicon carbide, whose chemical formula is SiC.

[0057] Step 3: ball milling wet mixing: adding the graphene suspension and zirconium oxide grinding balls to the mixture A, and ball milling on a planetary ball mill to obtain a mixture B;

[0058] The ball milling speed is 500 r / min, the ball milling time is 10 hours, and the graphene and ceramic powder are fully mixed by mechanical stirring.

[0059] Step 4: Drying: Drying the mixture B in a vacuum drying oven to obtain a dry powder C;

[0060] The drying time is 12 hours, the drying temperature is 120° C., and the dried powder C is a composite powder in which graphene and ceramic powder are uniformly mixed.

[0061] Step 5: Filling the mold, screening the powder C to obtain powder with uniform particles and pouring it into a graphite mold, padding the upper and lower parts of the mold with carbon paper, placing a pressure head, and pre-pressing it on a hydraulic pump to obtain a green body D;

[0062] The preloading pressure is 20MPa and the preloading time is 10min.

[0063] Step 6: Sintering: Place the pre-pressed graphite mold into the sintering furnace chamber, close the valve and evacuate to less than 10 MPa to start sintering at two temperatures, and grind the surface of the green body D after sintering to obtain an ultra-high temperature ceramic composite material;

[0064] The sintering heating rate was 15°C / min, the first sintering temperature was 1800°C, and the second sintering temperature was 2150°C.

[0065] Under 500°C conditions, after the introduction of graphene, the thermal shock test of the ceramic composite material sample was able to retain 86% of the initial strength value.

[0066] The composite material was processed into high-temperature tensile specimens. According to GJB8736-2015 test method for room-temperature tensile properties of continuous fiber reinforced ceramic matrix composites, the tensile strength at 1800°C was 221 MPa.

[0067] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing an ultra-high temperature ceramic composite material, characterized in that: The following steps are involved: Step 1, suspension preparation: graphene powder and deionized water are mixed at a mass ratio of 0.3 to 5:1 to prepare a solution, which is placed in an ultrasonic generator for ultrasonic treatment at a frequency of 150 kHz, and then transferred into a centrifuge for centrifugation at a speed of 3000 r / min, and the supernatant is taken to obtain a graphene suspension; Step 2, powder mixing: uniformly mixing ultra-high temperature ceramic powder and sintering aid in a mass ratio of 1:2.5-3.5 to obtain a mixture A; Step 3, ball milling wet mixing: adding graphene suspension and zirconium oxide grinding balls to mixture A, and ball milling on a planetary ball mill to obtain mixture B; Step 4: Drying: Drying the mixture B in a vacuum drying oven to obtain a dry powder C; Step 5: Mold filling: Powder C is screened to obtain powder with uniform particles and poured into a graphite mold. Carbon paper is placed on the upper and lower sides of the mold and a pressure head is placed in the mold. The mold is pre-pressed on a hydraulic pump to obtain a green body D. Step 6, sintering: put the pre-pressed graphite mold into the sintering furnace chamber, close the valve and evacuate to less than 10MPa to start sintering in two stages. After sintering, grind the surface of the green body D to obtain the ultra-high temperature ceramic composite material.

2. The method for preparing an ultra-high temperature ceramic composite material according to claim 1, characterized in that: The ultra-high temperature ceramic powder in step 2 is zirconium diboride, and the sintering aid in step 2 is silicon carbide.

3. The method for preparing an ultra-high temperature ceramic composite material according to claim 1, characterized in that: The ball milling speed in step 3 is 300-500 r / min, and the ball milling time is 5-10 hours.

4. The method for preparing an ultra-high temperature ceramic composite material according to claim 1, characterized in that: The drying time in step 4 is 8 to 12 hours, and the drying temperature is 80 to 120°C.

5. The method for preparing an ultra-high temperature ceramic composite material according to claim 1, characterized in that: The pre-pressing pressure in step 5 is 20 MPa, and the pre-pressing time is 10 min.

6. The method for preparing an ultra-high temperature ceramic composite material according to claim 1, characterized in that: The sintering heating rate in step six is ​​5-15°C / min, the first sintering temperature is 1800°C, and the second sintering temperature is 2150°C.

7. An ultra-high temperature ceramic composite material, characterized in that: Prepared according to the method described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Ultrahigh-temperature ceramic composite material and preparation method

    CN112028635A

  • Preparation method of high-toughness boride-carbide composite ceramic

    CN102503427A

  • Method for preparing ZrB2-based ultrahigh-temperature ceramic by spark plasma sintering of nano powder

    CN112159235A